Revisiting the controversial issue of tropical tropospheric temperature trends. Issue 11 (10th June 2013) - Mitchell, D. M.; Thorne, P. W.; Stott, P. A.; Gray, L. J.
<x xml:space="preserve">Abstract</x> [1] Controversy remains over a discrepancy between modeled and observed tropical upper tropospheric temperature trends. This discrepancy is reassessed using simulations from the Coupled Climate Model Inter‐comparison Project phase 5 (CMIP 5) together with radiosonde and surface observations that provide multiple realizations of possible "observed" temperatures given various methods of homogenizing the data. Over the 1979–2008 period, tropical temperature trends are not consistent with observations throughout the depth of the troposphere, and this primarily stems from a poor simulation of the surface temperature trends. This discrepancy is substantially reduced when (1) atmosphere‐only simulations are examined or (2) the trends are considered as an amplification of the surface temperature trend with height. Using these approaches, it is shown that within observational uncertainty, the 5–95 percentile range of temperature trends from both coupled‐ocean and atmosphere‐only models are consistent with the analyzed observations at all but the upper most tropospheric level (150 hPa), and models with ultra‐high horizontal resolution (≤ 0.5° × 0.5°) perform particularly well. Other than model resolution, it is hypothesized that this remaining discrepancy could be due to a poor representation of stratospheric ozone or remaining observational uncertainty.